2008
DOI: 10.1103/physrevc.78.055802
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation experiment onAu197and its implications for the dipole strength in heavy nuclei

Abstract: The 197 Au(γ, n) reaction is used as an activation standard for photodisintegration studies on astrophysically relevant nuclei. At the bremsstrahlung facility of the superconducting electron accelerator ELBE (Electron Linear accelerator of high Brilliance and low Emittance) of Forschungszentrum Dresden-Rossendorf, photoactivation measurements on 197 Au have been performed with bremsstrahlung endpoint energies from 8.0 to 15.5 MeV. The measured activation yield is compared with previous experiments as well as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 52 publications
4
25
0
Order By: Relevance
“…Measurements were performed with continuousenergy bremsstrahlung photons [25,26,27,28,29] and quasi-monoenergetic photons from Laser Compton Backscattering (LCB) [30,31,32] (see [33] as review). In near future, also tagged photons will be available with high energy resolution in the astrophysically relevant energy range at the low-energy photon tagger NEPTUN at the S-DALINAC, Darmstadt [34,35].…”
Section: Experiments On Photon-induced Reactionsmentioning
confidence: 99%
“…Measurements were performed with continuousenergy bremsstrahlung photons [25,26,27,28,29] and quasi-monoenergetic photons from Laser Compton Backscattering (LCB) [30,31,32] (see [33] as review). In near future, also tagged photons will be available with high energy resolution in the astrophysically relevant energy range at the low-energy photon tagger NEPTUN at the S-DALINAC, Darmstadt [34,35].…”
Section: Experiments On Photon-induced Reactionsmentioning
confidence: 99%
“…Using tagged photons at the NEPTUN facility [32,33] will allow to close the gap between the IVGDR and the low-energy strength. At this new experimental site, photon-induced experiments can be studied independently of limitations due to the particle thresholds, which will also play an important role in extending systematics on photon-induced reactions for nuclear astrophysics [34, 35,36,37]. On exotic nuclei, further systematics will be collected in order to confirm the dependence of the PDR on the neutron excess and also to connect to the experiments on the stable isotopes.…”
Section: Discussionmentioning
confidence: 99%
“…14) in the energy range of 8.23-12.17 MeV. A comparison with the photoactivation data of Nair et al 13) is not feasible because the data is available only in the form of activation yield. The cross section by Varlamov et al 30) is also shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, photoactivation measurements for Au have been extended from the threshold to the peak energy region of GDR. 13) Photoneutron cross sections for Au were previously measured as reference data for determining 152 Sm(,n) cross sections with LCS -rays at the National Institute of Advanced Industrial Science and Technology (AIST). 14) However, a data reduction by the photon difference method has ended up with large uncertainties.…”
Section: )mentioning
confidence: 99%